Epigenetics: the functional memory of ribosomal genes - Viegas, Wanda (2007)
The functional importance of Epigenetics arise from DNA sequencing programs that show the need for another code to explain the dynamics of gene expression patterns observed along cell differentiation and organism development. In this context, the study of ribosomal gene silencing is in fact an excellent model to better understand the relationships that are established between gene transcription and chromatin topology, and to unravel the epigenetic switches evolved in the framework of gene expression.